Pengaruh Institusional Structures, Trust In Seller, Seller Past Performance, Perceived Risk, dan Customer Satisfaction Terhadap Transaction Intentions di Situs Kaskus - Asaputra, Kevin; Wibisono, Handoyo (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2016)
AbstrakKredibilitas penjual yang baik dalam bisnis online akan meningkatkan kepercayaan konsumen pada perusahaan, menurunkan persepsi risiko, meningkatkan kepuasan dan meningkatkan niat untuk melakukan pembelian ulang. Selain kredibilitas penjual dalam bisnis online, informasi mengenai kinerja penjual di masa yang lampu juga merupakan informasi yang dapat digunakan sebagai referensi pembentukan kepercayaan konsumen. Kepercayaan yang dimiliki konsumen juga memberikan pengaruh terhadap kepuasan konsumen saat transaksi bisnis melalui media online.Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh institutional structures (buyer-driven certification, auction house escrow dan credit card guarantee) dan seller past performance terhadap trust in seller, mengetahui pengaruh trust in seller dan seller past performance terhadap perceived risk, mengetahui pengaruh trust in seller dan seller past performance terhadap customer satisfaction, mengetahui pengaruh trust in seller, perceived risk, customer satisfaction dan seller past performance terhadap transaction intentions, dan mengetahui perbedaan penilaian konsumen pada variabel institusional structures (buyer-driven certification, auction house escrow dan credit card guarantee), trust in seller, perceived risk, customer satisfaction, seller past performance dan transaction intentions berdasarkan perbedaan karakteristik konsumen.Hasil penelitian menunjukkan bahwa institusional structures (buyer-driven certification, auction house escrow dan credit card guarantee), trust in seller, customer satisfaction, dan seller past performance memberikan pengaruh yang positif terhadap niat pembelian konsumen dalam bisnis online. Persepsi risiko pada penelitian ini tidak memiliki pengaruh terhadap niat pembelian konsumen dalam bisnis online. Kata kunci: Efektivitas Pemasaran, Persepsi Risiko, Seller Past Performance, Transaction Intentions, Trust in Seller. AbstractGood seller’s credibility in the online business will boost consumer confidence in the company, lowering the perceived risk, increase customer satisfaction and increase intention to make repeat purchases. In addition to the seller's credibility in the online business, information on the performance of the seller in the future also light is information that can be used as a reference establishment of consumer confidence. The trust that consumers would be effect on consumer satisfaction when business transactions through online media.This study was conducted to determine the effect of institutional structures (buyer-driven certification, auction house escrow and credit card guarantee) and the seller the past performance of the trust in the seller, knowing the effect of trust in the seller and the seller the past performance of the perceived risk, knowing the effect of trust in seller and the seller past performance on customer satisfaction, knowing the effect of trust in the seller, perceived risk, customer satisfaction and the seller the past performance of the transaction intentions, and knowing the difference of consumer ratings on variable institutional structures (buyer-driven certification, auction house escrow and credit card guarantee), trust in the seller, perceived risk, customer satisfaction, seller past performance and transaction intentions based on different characteristics of the consumer.The results showed that the institutional structures (buyer-driven certification, auction house escrow and credit card guarantee), trust in the seller, customer satisfaction, and past performance sellers provide a positive influence on consumer purchase intentions in the online business. The perception of risk in this study had no influence on consumer purchase intentions in the online business. Keywords: Marketing Effectiveness, Risk Perception, Seller Past Performance, Transaction Intentions, Trust in Seller.